A Review of Research on the Effects of LREs on L2 Development (Asian Education Studies, 2016)
Swain and Lapkin’s (1998, 2001, 2002) language-related episodes (LREs) have generated greater interest among ESL (English as a Second Language) practitioners and researchers on the effects of addressing linguistic issues during learner-learner interaction in the course of completing pedagogic tasks on interlanguage development. This paper reviews the results of various studies that measured the effects of LREs on L2 development. This paper concludes that LREs could have beneficial effects on L2 learning as reflected by the amount of negotiation and learning opportunities that occurred, the rate of successful outcomes of the repair practices, and L2 achievements in posttests. This paper also suggests that future research could further analyse the exchanges that occur during LREs to gain a greater understanding of interaction-oriented learning opportunities.